Uso de produtos biológicos no controle de fitonematoides na cultura da soja - IRYANA LAURA QUEIROZ VIANA (2024)
USE OF BIOLOGICAL PRODUCTS TO CONTROL PHYTONEMATOIDS IN SOYBEAN CROPS ABSTRACT: Phytonematodes are obligate plant parasites that cause significant damage to crops, leading to yield losses and economic impacts in several regions. Proper management practices are essential to maintain populations of these parasites below the economic damage level. This study aimed to evaluate the efficacy of different bacterial species (applied alone or in combination) in minimizing damage caused by the phytonematodes Pratylenchus brachyurus and Heterodera glycines to soybean plants. The experiment was conducted in a randomized block design, with 8 treatments and 4 replications. The treatments consisted of a negative control (no application of products; T1), a positive control (application of fluopyram fungicide; T2), and applications of bacteria: Bacillus mojavensis + B. pumilus + Priestia megaterium + B. amyloliquefaciens (T3); B. amyloliquefaciens + 2 strains of B. subtilis + P. megaterium + B. licheniformis (T4); B. subtilis + B. velezensis (T5); B. methylotrophicus + B. subtilis (T6); Bacillus amyloliquefaciens (T7), and B. subtilis + B. polymyxa + P. megaterium + B. pumilus + B. amyloliquefaciens + B. licheniformis (T8). Treatments were applied to the planting furrows during sowing. Soil and root samples were collected 30 and 60 days after planting to analyze the treatment efficacy. Data on the number of eggs, population of P. brachyurus and H. glycines, and some agronomic parameters were subjected to analysis of variance, and means were compared using the ScottKnott test at 5% significance level. Treatment efficacy was assessed using Abbott's formula. The number of eggs and nematodes of P. brachyurus and H. glycines, in both soil and roots, was reduced after applying the different bacterial species compared to positive and negative controls. The combination of multiple bacterial species improved the suppression of populations of these phytopathogens, differing from the chemical fungicide. Among the phytotechnical parameters evaluated, biological treatments proved superior to chemical treatments concerning productivity. Keywords: Growth-promoting bacteria. Rhizobacteria. Biological control. Phytopathogenic nematodes. Pratylenchus brachyurus, Heterodera glycines.